Биоинженерные аспекты моделирования программного интерфейса пользователя - Аверьянова, Л. А. (ХНУРЭ, 2008)
The bioengineering aspects of user interface design are considered as the main component of human-computer interaction. The necessity of individual adaptive simulation of user workspace and features at initial stage of interface design is noted. Such approach allows greatly increase efficiency of created software.
Keywords: биоинженерия; интерфейс пользователя